Investigation of the Characteristic Properties of Glacial Acetic Acid-Catalyzed Carbon Xerogels and Their Electrochemical Performance for Use as Electrode Materials in Electrical Double-Layer Capacitors - Nguyen Khanh Nguyen Quach; Wein-Duo Yang; Zen-Ja Chung; Hoai Lam Tran; Rui Liu (Advances in Materials Science and Engineering)
Glacial acetic acid was used as a catalyst in the preparation process of carbon xerogels from the condensation of resorcinol and formaldehyde for shortening significantly the gelation time. The effect of the resorcinol/catalyst ratio over a large range of 2 to 500, the solvent exchange manner with acetone, and the pyrolysis temperature of 700 to 1000°C on the characteristic properties of the carbon xerogels were investigated. A resorcinol/catalyst ratio of 2 and a pyrolysis temperature at 800°C were found to be the optimal condition for the preparation of carbon xerogels with a well-balanced porosity between micro- and mesopores, high surface area (577.62 m2g−1), and large pore volume (0.97 cm3g−1), which are appropriate for use as electrode materials in an electrical double-layer capacitor. The carbon xerogel electrodes that were prepared under these optimal conditions exhibited a good electrochemical performance with the highest specific capacitance of 169 Fg−1 in 6 M KOH electrolyte at a scan rate of 5 mVs−1 from cyclic voltammetry.